Implementasi Ajaran Islam dalam Pelestarian Alam: Analisis Religiusitas, Literasi Ekologi, dan Perilaku Lingkungan Masyarakat Dompu - Abdullah; Nasrulloh (Al-Kindi, 2026)
Objective study qualitative This is For understand How Islamic teachings are used For preservation natural through religiosity , literacy ecology , and action public Dompu to environment . Data collected through interview comprehensive with activist environment , religious figures , and society as well as observation field to action daily related with management nature . Study show that trust religious people of Dompu play role important in build awareness environment , especially through interpretation verses that speak about obligation guard earth and prevent damage ( facade ). Islamic teaching in mosques, assemblies religious studies and traditions local push literacy ecology . On the other hand , the action environment public like reforestation , conservation land , and reduction rubbish appear as form internalization religious values in life real . According to study this , strengthens ethics ecological and encouraging initiative preservation nature in Dompu can achieved through combination Islamic values and knowledge environment.